The Cybersecurity Dilemma: considerations for investigations in the Dark Web - Niekerk, Brett van (Acta criminologica, 2018)
The Dark Web is a ‘hidden’ portion of the Web which is un-indexed by major search engines, and is widely used by criminals, political activists, government agencies and others to conduct a range of activities, both benign and illegal. As with most possible crimes, there is the need for law enforcement to investigate, resulting in them needing to venture onto the Dark Web to investigate a crime that has occurred online, or activity supporting crime in the physical world. However, law enforcement activity online may be noticed by other nations and be misinterpreted. The Cybersecurity Dilemma draws from the international relations principle, the Security Dilemma or Spiral Model, where two nations, seeking to increase their security and prevent conflict, in fact tend to result in escalating the conflict through misinterpretations of each other’s actions due to mistrust. In Cyberspace, it is more difficult to ascertain intentions, therefore the misinterpretation of online activity may also result in the escalation of cyber conflict. The aim of this article is to illustrate the possibility of escalation in Cyberspace using Game Theory, whereby this may emerge as a possible challenge to law enforcement investigations on the Dark Web.